2015
DOI: 10.1074/mcp.m114.040345
|View full text |Cite|
|
Sign up to set email alerts
|

N-linked (N-) Glycoproteomics of Urimary Exosomes*

Abstract: Epithelial cells lining the urinary tract secrete urinary exosomes (40 -100 nm) that can be targeted to specific cells modulating their functionality. One potential targeting mechanism is adhesion between vesicle surface glycoproteins and target cells. This makes the glycopeptide analysis of exosomes important. Exosomes reflect the physiological state of the parent cells; therefore, they are a good source of biomarkers for urological and other diseases. Moreover, the urine collection is easy and noninvasive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 38 publications
(47 reference statements)
1
58
0
Order By: Relevance
“…Taken together, our glycomics study demonstrated the prevalence of complex N -glycans in all particle subsets with relatively high levels of sialylation, consistent with previous findings of complex N -glycans and sialoglycoproteins in tumor microvesicles/exosomes 25-27 . Furthermore, our study revealed differences in N- glycan composition and structures among exomeres, Exo-S, and Exo-L.…”
Section: Resultssupporting
confidence: 91%
“…Taken together, our glycomics study demonstrated the prevalence of complex N -glycans in all particle subsets with relatively high levels of sialylation, consistent with previous findings of complex N -glycans and sialoglycoproteins in tumor microvesicles/exosomes 25-27 . Furthermore, our study revealed differences in N- glycan composition and structures among exomeres, Exo-S, and Exo-L.…”
Section: Resultssupporting
confidence: 91%
“…examined urinary exosome glycosylation patterns because the exosome glycosylation pattern influences exosome targeting and uptake [98]. 37 glycoproteins were identified in urinary exosomes by comparing the urinary exosome glycan structures to a database rather than through iterative de novo glycan structure analysis [98]. Glycoproteins were digested with trypsin prior to enrichment by Sambucus nigra agglutinin (SNA) affinity chromatography or size exclusion chromatography.…”
Section: Urinary Glycoproteomicsmentioning
confidence: 99%
“…SNA binds preferentially to sialic acid attached to terminal galactose in α-2,6 and to a lesser degree, α-2,3 linkages. The glycoprotein enriched fractions were analyzed using collision induced dissociation-Tandem MS [98]. From these glycoproteins, 126 N -glycopeptides from 51 N -glycosylation sites were characterized [98].…”
Section: Urinary Glycoproteomicsmentioning
confidence: 99%
“…The different programs utilize various strategies to identify N-glycopeptides including the use of characteristic Y 1 ions, oxonium ions, B/Y-and C/Z-type glycan fragment ion series, and b/y-and c/z-type peptide fragment ions (116,117). In order to limit the search space and enhance the detailed structural knowledge of the glycans encountered in a given glycoproteome, several studies have performed parallel N-glycome profiling (21,40,88,105,106,108,162). This so-called 'glycomics-assisted glycoproteomics' approach can also be complemented with quantitative proteome and de-N-glycoproteome profiling (mapping of formerly N-glycosylated peptides) (21, 46, 88, 103, 105-108, 135, 159, 162), which reduce the search space even further and provide supporting evidence to pinpoint the exact mechanism(s) driving the observed glycoproteome alterations.…”
Section: Ms Acquisition Strategies In Glycoproteomics-lc-ms/mentioning
confidence: 99%
“…Other new enrichment methods of interest include the metabolic incorporation of N-azido sugars into N-glycopeptides to facilitate their specific enrichment and detection (84,85). The selective precipitation of glycopeptides by acetone (86), use of size exclusion chromatography (87,88) and the combined use of porous graphitized carbon (PGC) and reversed phase (RP) (89) and titanium dioxide (90) solid phase extraction (SPE) for efficient enrichment of glycopeptides and sialoglycopeptides, respectively, are also promising developments. However, common for most of these proof-of-principle methodology studies is the need for further validation to demonstrate their true potential in glycoproteomics.…”
mentioning
confidence: 99%